(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
We are facing the challenge of increasing application of new technological solutions in the public administration among which are the concept of ontology and the increasing exchange of knowledge and information with which we deal in this paper. This should be the primary drivers of power for the transition of work of the public administration to the new concept of e-m-i-Government. In this paper we perceive the IT situation in this region, development trend of ontology in the public administration and we suggest the solutions for public administration in Bosnia and Herzegovina to implement new solutions. In this paper we suggest the process organization of work and serving in the public administration as a basis for more efficient and more effective implementation of ontologies and the exchange of knowledge with the use of new technological solutions. Likewise, we propose the solution which is based on a single access point for all service users regardless of the communication channel. The implementation of ontologies and intelligence in the public administration will observe as the basis for offering services, personalization and self-service.